Prevention Of Dental Caries In Children with Convulsions The Disease is Treated - Rajabov А.А. (Research Parks Publishers, 2021)
A chronic brain disease characterized by repeated spontaneous seizures (paroxysms) that occur as a result of excessive neural discharges. Clinically, epilepsy is manifested by convulsions and changes in consciousness (up to its loss) Epilepsy can be either an independent disease or a symptom of another pathology. According to the WHO, approximately every 4-10 people out of 1000 suffer from active epilepsy worldwide — this is one of the most common neurological diseases. Epilepsy has been known to mankind for a long time — the first known mention of epilepsy came to us from 500-700 BC.